Antiplasmodial constituents from the stem bark of Polyalthia longifolia var pendula. (March 2015) - Annan, Kofi; Ekuadzi, Edmund; Asare, Cindy; Sarpong, Kwame; Pistorius, Dominik; Oberer, Lukas; Gyan, Ben A.; Ofori, Michael
Graphical abstract: Highlights: We investigated Polyalthia longifolia for its antiplasmodial potential. Fractionation of the chloroform extract led to the isolation of four novel compounds. We report that these compounds possess antiplasmodial effects and may be responsible at least in part for its traditional use as an antimalarial remedy. Abstract: Along with two known compounds (1 and2), four new clerodane diterpenes were isolated and identified from the stem bark of Polyalthia longifolia : cleroda-3-ene pyrrole-15, 16-dione (3 ), cleroda-3-ene, pyrrolidine-15, 16-dione (4 ), cleroda-3, 13(14)E-diene-15, 16-diamide (5 ), and cleroda-3-ene-15, 16-diamide (6 ). Their structures were elucidated by combinations of NMR, MS and IR. Using the WHO Mark III Microtest assay, the isolated compounds were evaluated for their antiplasmodial effects. They showed antiplasmodial effects, with IC50 s ranging from 4.5 to 213.8 μM.